An Ex-Ante Evaluation of the Impact of Social Insurance Policies on Labor Supply in Brazil : The Case for Explicit Over Implicit Redistribution - Robalino, David A.; Zylberstajn, Eduardo; Zylberstajn, Helio; Afonso, Luis Eduardo (World Bank, Washington, DC, 2014)
This paper solves and estimates a stochastic model of optimal inter-temporal behavior to assess how changes in the design of the income protection and pension systems in Brazil could affect savings rates, the share of time that individuals spend outside of the formal sector, and retirement decisions. Dynamics depend on five main parameters: preferences regarding consumption and leisure, preferences regarding formal Vs. informal work, attitudes towards risks, the rate of time preference, and the distributions of two exogenous shocks that affect movements in and out of the social security system (independently of individual decisions). The yearly household survey is used to create a pseudo panel by age-cohorts and estimate the joint distribution of model parameters based on a generalized version of the Gibbs sampler. The model does a good job in replicating the distribution of the members of the cohort across states (in or out of them social security / active or retired). Because the parameters are related to individual preferences or exogenous shocks, the joint distribution is unlikely to change when the social insurance system changes. Thus, the model is used to explore how alternative policy interventions could affect behaviors and through this channel benefit levels and fiscal costs. The results from various simulations provide three main insights: (i) the Brazilian SI system today might generate unnecessary distortions (lower savings rates, less formal employment, and more early retirement) that increase the costs of the system and might generate regressive redistribution; (ii) there are important interactions between the income protection and pension systems, which calls for joint policy analysis when considering reforms; and (iii) current distortions could be reduced by creating an actuarial link between contributions and benefits and then giving matching contributions or matching capital to individuals with limited savings capacity, which requires having individual savings accounts that can be funded or notional.